A Qualitative Study on Mindfulness and Teacher’s Well Being - Rizwana Muneer .; Rida Batool Batool (Ilmu Inovasi Nusantara, 2021)
Teaching is one of the most stressful occupation. Especially the teachers who have recently started their career are the one’s who suffer from stress the most. Copping up with the stress should be taught to them by making them aware of the concept of mindfulness. The study is conducted to see the effect of mindfulness practices on the stress level of the teachers. The study is descriptive and purely qualitative in nature. Population of the study is private school teachers and the sample size is based on 2 primary school teachers who have recently started teaching and facing difficulties in coping up with the stress. The sampling technique used in the study is Purposive non- random sampling. The data collection tool for study is Interview and analyzed by thematic analysis. The overall results of the conducted study is that Mindfulness activities like Mindfulness breathing ,Body scan, Mindfulness through nature, Japanese method to relax in 5 minutes can help a lot to reduce teacher’s stress